Strategies to develop speaking skills among Malay learners of Arabic - Che Haron, Sueraya; Sheikh Ahmad, Ismail; Mamat, Arifin; Ahmed Mohamed, Ismaiel Hassanein (Centre for Promoting Ideas, USA, 2012)
Learning L2/FL in the outside world or in societies where the language is in actual use can be more meaningful, as compared to learning it inside the classroom. Most of the time learners are not able to develop much functional ability, as a result of limited opportunity to use the L2/FL in the classrooms. However, research shows that one of the things that characterizes good language learners is their ability to make use of their class learning to develop their speaking skills. Therefore, the role of classrooms should not be denied. This paper describes a study involving good and poor Malay speakers of Arabic, to investigate the strategies used by them to develop Arabic speaking skills in the classroom. It highlights the similarities and differences of the strategies used by both groups of speakers. Finally, the paper suggests some strategies for teachers to help increase the opportunities to develop Arabic speaking skills in the classroom.